Case Report: Identification of a de novo Missense Mutation in the F8 Gene, p.(Phe690Leu)/c.2070C > A, Causing Hemophilia A: A Case Report - Bai, Haiyan; Xue, Xia; Tian, Li; Liu, Xi Tong; Li, Qian (Frontiers in Genetics, 2021)
Hemophilia A is an X-linked recessive bleeding disorder caused by various types of pathological defects in the factor VIII gene (F8/FVIII). Preimplantation genetic testing for monogenic disease (PGT-M) is a powerful tool to tackle the transmission of monogenic inherited disorders from generation to generation. In our case, a mutation in F8 had passed through female carriers in a hemophilia A family and resulted in two male patients with hemophilia A. To identify the etiological genetic variants of F8, Next-generation sequencing (NGS) was used for chromosome copy number variation detection, Sanger sequencing to verify mutation sites, single nucleotide polymorphism (SNP) for site amplification, and sequencing to validate the genetic linkage. Finally, a novel missense mutation, p. (Phe690Leu)/c.2070C>A, occurring in exon 13 of F8, was screened out as a pathogenic mutation. Following this, an F8 normal euploid blastocyst was transferred. At the 18th week, the pregnant mother underwent amniocentesis, NGS, Sanger sequencing and SNP typing further confirmed that the fetus had a healthy genotype. After delivery, a neonatal blood sample was sent for FVIII concentration detection, and the result established the FVIII protein was rescued to a nearly average level. We first identified a new type of pathogenic mutation in F8, which has not been previously reported, selected a genetically healthy progeny for an affected family, and provided valuable knowledge of the diagnosis and treatment of hemophilia A.